Efektifitas Edukasi Berbasis Family Centered Maternity Care terhadap Dukungan Keluarga dan Self Efficacy pada Ibu Postpartum dalam Pemberian Asi (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the effectiveness of family centered maternity care-based education on family support and self-efficacy for postpartum mothers in breastfeeding. The method used is quantitative research with a quasi-experimental design with a pretest and posttest design with a control group. The sample in this study consisted of 52 respondents. The research instrument used a family support questionnaire modified from Nasution's family support questionnaire (2007) and a self-efficacy instrument using the Breastfeeding Self-efficacy Scale-Short Form (BSES-SF). Data analysis used the Paired T-Test and Independent T-Test. The results of research on the effectiveness of interventions on family support, P-Value 0.000 and self-efficacy 0.004. The conclusion is that education based on Family Centered Maternity Care is effective in increasing family support and self-efficacy for postpartum mothers in breastfeeding.  Keywords: Education, Family Support, Family Centered Maternity Care, Self efficacy